PENINGKATAN KINERJA KEUANGAN USAHA MIKRO KECIL DAN MENENGAH MELALUI LITERASI KEUANGAN, PENGGUNAAN TEKNOLOGI, DAN PERILAKU KEUANGAN - Anita Erari (JURNAL ILMIAH EDUNOMIKA, 2024)
This research is motivated by the importance of improving the financial performance of MSMEs. The purpose of this study is to know and analyze the influence of Financial Literacy, Technology Use, and Financial Behavior on the Financial Performance of Micro, Small and Medium Enterprises. The research method used in this study is quantitative research method. The population in this study is 59 student MSMEs in Jayapura City. The sampling method is non-probability sampling with total sampling techniques. The reason for taking total sampling is because the total population is less than 100 the entire population is used as a research sample. So the number of samples in this study is as many as 59 student MSMEs in Jayapura City. The collected data were tested for validity, reliability, classical assumption tests and multiple linear regression analysis. The results of this study revealed 1) Financial Literacy has a significant effect on the financial performance of student MSMEs. 2) The use of technology has a significant effect on the financial performance of MSME students in Jayapura City. 3) Financial Behavior has a significant effect on the financial performance of student MSMEs in Jayapura City and 4) Financial literacy, the use of technology, and financial behavior affect the financial performance of student MSMEs in Jayapura City.